Serum ghrelin levels are enhanced in patients with epilepsy - Berilgen, MS; Mungen, B; Ustundag, B; Demir, C (W B Saunders Co Ltd, 2006)
Purpose: In patients with epilepsy, although many changes in the physiology of hormones in the neuroendocrine system can occur (especially in the sex hormones, for example), the causes of these changes have not been fully elucidated. There are also relations between seizure activity and stages of steep. Ghrelin is the peptide hormone, which has been shown to affect both endocrine function and steep. The purpose of this study was to evaluate serum levels of ghrelin in epilepsy patients. Methods: A total of 35 patients currently receiving antiepileptic drug therapy (of these patients, 20 had primary generalized seizure and 15 had partial seizure) were studied. The control group consisted of 30 healthy volunteers matched for age and gender. In all participants, serum levels of ghrelin, cholesterol and triglycerides were measured and body mass index (BMI) was determined. Patients with endocrine, immune or any other chronic diseases were excluded. Results: In the epilepsy patients, the mean serum ghrelin level was 158.81 +/- 155.97 pg/ml, and this was significantly higher than the control group's level of 93.43 +/- 21.33 pg/ml (p < 0.001). In terms of serum cholesterol, triglycerides and BMI, no significant differences were found between the epilepsy patients and the control group (p > 0.05). Conclusions: The origin of higher serum ghrelin levels in epilepsy and their relation to seizures are not completely known. However, this elevation of serum ghrelin could contribute to the lengthening of NREM steep in epilepsy patients, thereby playing a rote in seizure occurrence. From another direction, high serum ghrelin levels could cause changes and/or dysfunction in hormone secretion and physiology via its effects on growth hormone, and thereby play a facilitating role in seizure occurrence. (c) 2006 British Epilepsy Association. Published by Elsevier Ltd. All. rights reserved.
Keywords: epilepsy; ghrelin; neuroendocrine system; sleep